2005
DOI: 10.1159/000086557
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Childhood Brain Tumors in Syria (1993–2002)

Abstract: Objective: To determine whether the incidence and location of childhood CNS tumors in Syria follows the same pattern described in Western and Far Eastern countries. Patients and Methods: We analyzed the data compiled from 367 children with brain tumors operated on in our Department of Neurosurgery between 1993 and mid-2002. We excluded all vascular and metastatic lesions and adopted the latest WHO classification in grouping all glial tumors. Results: We found that 47% of brain tumors were located in the suprat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
45
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 31 publications
13
45
3
Order By: Relevance
“…7 Medulloblastoma was the most common tumor seen in children (13%) in our study which is similar to many other studies. 8 Certain tumors are common in adults and certain tumors are common in adults which were observed in our study. Meningiomas are commonly seen in adults than in childhood which is consistent with our study.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…7 Medulloblastoma was the most common tumor seen in children (13%) in our study which is similar to many other studies. 8 Certain tumors are common in adults and certain tumors are common in adults which were observed in our study. Meningiomas are commonly seen in adults than in childhood which is consistent with our study.…”
Section: Discussionsupporting
confidence: 66%
“…Meningiomas are commonly seen in adults than in childhood which is consistent with our study. 3,8,9 In our study, 66% of cases were seen in adults. In our study, complete resection was done in 17 cases, complete resection was very difficult in these cases because of their location (Figure 4).…”
Section: Discussionsupporting
confidence: 44%
“…This insight, to some degree, was embodied in the revised World Health Organization (WHO) 2000 classification of nervous system tumors, which included the recognition of novel pathologic entities and variants as well as the deletion of some previously described variants [1]. Several studies of the epidemiology of childhood neurological neoplasms using the latest classification scheme have been conducted [2,3,4]. However, to date, no detailed survey has been conducted on the epidemiology of neurological tumors in children from China, a developing country with the largest population in the world.…”
Section: Introductionmentioning
confidence: 99%
“…This result reflects the variation in the distribution of brain tumors between population where a study from Syria [22] demonstrated that the most common tumor found in Syrian children was medulloblastoma (27.5%), followed by astrocytoma (25.8%) then craniopharyngioma (14.1%).…”
Section: Discussionmentioning
confidence: 64%